ANALISIS DAMPAK BELANJA SUBSIDI, BELANJA BANTUAN SOSIAL DAN PERTUMBUHAN EKONOMI TERHADAP KEMISKINAN DI PROVINSI MALUKU - Pierre Fernic Engko; Muhammad Bugis; M. K. Tupamahu; Maryam Sangadji (JURNAL ILMIAH EDUNOMIKA, 2024)
The research aimed to find out the impact of subsidy spending, social assistance spending and the economic growth in Maluku Province since 2012 - 2021. The data used of the research is secondary data from the Indonesian Central Bureau of Statistics and data from the Finance Ministry of Indonesia as well as others supporting data. The multiple linear regression method using Eviews10 application which was used as a tool to process data concluded that subsidy spending and social assistance spending had a positive and insignificant effect on reducing poverty in Maluku Province and The Economic Growth had a negative and significant effect.